Extended trochanteric osteotomy: improving the access and reducing the risk in revision THA - Wronka, Konrad Sebastian (EFORT Open Rev, 2020)
This review article presents a comprehensive literature review regarding extended trochanteric osteotomy (ETO). The history, rationale, biomechanical considerations as well as indications are discussed. The outcomes and complications as reported in the literature are presented, discussed and compared with our own practice. Based on the available evidence, we present our preferred technique for performing ETO, its fixation, as well as post-operative rehabilitation. The ETO aids implant removal and enhanced access. Reported union rate of ETO is high. The complications related to ETO are much less frequent than in cases when accidental intra-operative femoral fracture occurred that required fixation. Based on the literature and our own experience we recommend ETO as a useful adjunct in the arsenal of the revision hip specialist. Cite this article: EFORT Open Rev 2020;5:104-112. DOI: 10.1302/2058-5241.5.190005